Characterization, histological evaluation and efficacy of docetaxel-loaded cockle shellderived CaCO3 nanoparticles in vitro and in vivo - Hammadi, Nahidah Ibrahim (2018)
Breast cancer is one of the most widely researched cancers worldwide. Currently, therapeutic options aimed at reducing its metastasis have a limitation of toxicity to the patient. Cockle shell-derived calcium carbonate aragonite nanoparticles (CSCaCO3NP) have shown promising potentials as a slow drug releasing compound in cancer chemotherapy. This study explores CSCaCO3NP as a delivery system aimed at enhancing docetaxel (DTX) release in breast cancer. Furthermore, this study also evaluated the in vitro cytotoxicity of DTX-loaded CSCaCO3NP against 4T1 cell line, and in vivo toxicity evaluation of CSCaCO3NP, and the effect of DTX-loaded CSCaCO3NP in 4T1 cancer-bearing Balb/C mice. The nano-anticancer formulation (DTX-CSCaCO3NP) was characterized by various physico-chemical characterizations. The in vitro cytotoxicity evaluation was achieved using different bioassay parameters. The pharmacokinetic study was estimated. The in vivo mice acute and sub-chronic toxicity studies were conducted for 14 days. In the therapeutic study, mice were subcutaneously inoculated with 5 x 105 4T1 cells in the right mammary fat pad. Tumor treatment commenced in two stages, the early and late stages. Mice were grouped into 3 treatment groups of DTX (10 mg/kg), DTXCSCaCO3NP (10 mg/kg) and DTX-CSCaCO3NP (5 mg/kg). The positive and negative control groups were also included. Characterization results revealed that DTX-CSCaCO3NP synthesis was excellent, and had a sustained release at pH 7.4. TEM results showed nanoparticles sizes of 42 nm. The XRD patterns revealed strong crystallizations and pure aragonite particles formulation, while FTIR showed entrapment between the drug and nanoparticles. The DTX-CSCaCO3NP had comparable (p>0.05) cytotoxicity effects as DTX against MCF-7 and 4T1 cells. Fluorescence and apoptosis assay showed higher (p<0.05) number of apoptotic cells in both DTX and DTX-CSCaCO3NP groups. SEM showed the presence of cellular blebbing, while TEM showed nuclear fragmentation, apoptosis and vacuolation. In in vivo toxicity analysis, no significant sign was observed and no mortality was recorded in both study periods. Tumor volume, organ weights, tumour inhibition rates and metastatic cells were significantly (p<0.05) lower in the DTX-CSCaCO3NP (10 mg/kg) group. In conclusion, the results showed that the formulated DTX-CSCaCO3NP released DTX slower at pH 7.4. It was also observed that DTX-CSCaCO3NP has similar anticancer effects on MCF-7 and 4T1 cells as DTX and since it has a slow release, CSCaCO3NP is a promising delivery system for DTX in the 4T1 induced breast cancer model. Hence, DTX-CSCaCO3NP (10 mg/kg) showed high efficacy against breast cancer metastasis.